Psychological Capital dan Innovative Work Behavior pada Perusahaan Tenun Ikat - Baharudin, Radhif Dimas Mahendra; Ekowati, Dian (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2022)
This study aims to examine and analyze the influence of Psychological Capital and other variables as a mediation that is thought to encourage Innovative Work Behavior, namely Employee Creativity and Employee Engagement, at two weaving companies. Respondents in this study were employees of the “Medali Emas” ikat weaving company totalling 120 people and the “Kodok Ngorek 2” ikat weaving company totalling 26 people. Tests in this study used data processing software, namely SmartPLS version 3.3.7. After testing, the results obtained that Psychological Capital has a positive and significant effect on Innovative Work Behavior, Employee Creativity and Employee Engagement. In addition, the test results also show a positive and significant influence between Employee Creativity and Employee Engagement in Innovative Work Behavior. Thus, Employee Creativity and Employee Engagement partially mediate the influence of Psychological Capital on Innovative Work Behavior in the employees of 2 ikat weaving companies in Bandar Kidul, Kediri.